Molecular epidemiology of measles virus in Italy, 2002–2007 - Magurano Fabio; Fortuna Claudia; Marchi Antonella; Benedetti Eleonora; Bucci Paola; Baggieri Melissa; Nicoletti Loredana (Virology Journal, 2012)
Abstract Background The European Regional Office of the World Health Organization (WHO/Europe) developed a strategic approach to halt the indigenous transmission of measles in its 53 Member States by 2015. In view of the goal of measles elimination, it is of great importance to assess the circulation of wild-type measles virus (MV). Genetic analysis is indispensable to understand the epidemiology of measles. Methods Urine and saliva samples were collected between May 2002 and December 2007, in order to find the origins and routes of wild type measles virus circulation. RT-PCR was performed on a total of 414 clinical samples of patients from different Italian regions. The results confirmed the genome presence in 199 samples, out of which 179 were sequenced. The sequences were genotyped by comparing the fragment coding for the carboxyl terminus of the nucleoprotein (450 nucleotides) with that one of the WHO reference strains. Results From the year 2002 to the year 2007 phylogenetic analysis of measles sequences showed a predominant circulation of the D7 genotype in the Italian territory for the years 2002–2004. This genotype was replaced by D4 and B3 genotypes in the biennium 2006–2007. During the same period C2, A, D5 and D8 genotypes were also detected. Conclusions Genetic characterization of wild-type MV provides a means to study the transmission pathways of the virus, and is an essential component of laboratory-based surveillance. Knowledge of currently circulating measles virus genotype in Italy will help in monitoring the success of the measles elimination programme and will contribute to evaluate the effectiveness of future vaccination campaigns.